PENERAPAN STRATEGI EKSPERIMEN DALAM UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA SD NEGERI 091423 AFD III BAH BOTONG TAHUN AJARAN 2022/2023 - Jubelando O Tambunan (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This research is motivated by the conditions of science learning at schools, where learning activities are still taking place conventionally, namely dominated by teachers so that students are less enthusiastic about participating in the science learning process and the low science learning outcomes on the subject of the properties of light. In this case the researchers tried to overcome these problems by using experimental methods in the science learning process in class. The focus of the research in this thesis are: 1) What is the learning process by applying the experimental method to improve science learning outcomes on the subject of the properties of light for fifth grade students at SD Negeri 091423 Affd. ill. Bah Butong academic year 2022/2023? 2) What are the results of studying science in the subject matter of the properties of light with the application of the experimental method for fifth grade students at SD Negeri 091423 Afd. III. Bah Butong academic year 2022/2023? This study aims to describe the learning process by applying the experimental method and knowing the results of science learning on the subject of the properties of light by applying the experimental method to fifth grade students at SD Negeri 091423 Afd. III. Bah Butong for the 2022/2023 academic year. In this study used data collection methods in the form of: tests, observations, interviews and field notes. Where tests are used to determine students' cognitive learning outcomes after experiencing the teaching and learning process, observation is used to observe the learning process and to determine affective and psychomotor learning outcomes, interviews are used to determine student responses, as well as to obtain the information needed, and field notes are used to complete the unrecorded data. The approach used is a qualitative approach and the type of research is classroom action research. After the writer carried out two cycles of classroom action research and obtained the necessary data from the existing facts, the researcher can draw the following conclusions: The science learning process on the subject of the properties of light goes through several stages, namely (1) the teacher conducts initial experiment, (2) students observe experiments, (3) students formulate temporary observations, (4) students conduct their own experiments, (6) students are able to apply and give examples, (7) the teacher gives an evaluation. While student learning outcomes in science learning through the application of experimental methods can increase from cycle I to cycle II. Cognitive aspects of learning outcomes increased by 13.9% while psychomotor aspects of learning outcomes increased by 13.8% and affective learning outcomes increased by 10.41%